(untitled) (Scientific journal of the Fergana State University, 2025)
The Kara Darya is one of the most significant rivers in the Fergana Valley, playing a crucial role in the formation of the region’s ichthyofauna. Since the second half of the 20th century, the impact of anthropogenic factors on the river has increased significantly. The construction of water dams has severely hindered fish migration. Additionally, after the 1970s, alongside fish species intentionally introduced from the rivers of the Far East for acclimatization, invasive species that were inadvertently introduced also contributed to a dramatic shift in the composition of the ichthyofauna of the Kara Darya. Furthermore, species that were once present in the river, such as Acipenser nudiventris, Pseudoscaphirhynchus fedtschenkoi, and Capoetobrama kuschakewitschi, have become entirely extinct in the Syr Darya basin. Recent studies confirm the presence of 28 fish species in the middle and lower reaches of the Kara Darya, belonging to six orders, 14 families, and 26 genera. This study examines the ichthyofaunal composition of the Kara Darya, its historical and recent changes, and the factors influencing fish diversity in the river.